2019
DOI: 10.1111/ffe.13174
|View full text |Cite
|
Sign up to set email alerts
|

Loading‐rate dependence of mode I crack growth in concrete

Abstract: Mode I crack propagation process of concrete under relatively low loading rates which cover four orders of magnitude (0.2 μm/s to 2.0 mm/s) is investigated with three‐point bending (TPB) beams. All measured material properties exhibit rate sensitivity and follow a log‐linear relationship with the loading rate. A rate‐sensitive softening curve is established. The complete load‐crack mouth opening displacement (P‐CMOD) curve, crack propagation length, and fracture process zone (FPZ) length are simulated based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For prefabricated cracked members, the determination of P ini can be accomplished through the test curve method and strain gauge method [ 21 , 35 , 36 ]. The test curve method takes the turning point from linear to non-linear in the rising section of P–CMOD curve as ; however, the turning point is difficult to determine precisely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For prefabricated cracked members, the determination of P ini can be accomplished through the test curve method and strain gauge method [ 21 , 35 , 36 ]. The test curve method takes the turning point from linear to non-linear in the rising section of P–CMOD curve as ; however, the turning point is difficult to determine precisely.…”
Section: Resultsmentioning
confidence: 99%
“…The larger the tension displacement of COD, the higher the consumed energy and peak load. Additionally, the results of pertinent research by Ma [ 21 ] and Zhu [ 23 ] have indicated that the fracture length and opening displacement increase with loading rate. BFAPC with 0.6% content had a smaller CTOD value but a longer crack propagation length at a strain rate of 10 −6 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the desired results were not obtained because crack growth might be unstable and asymmetric. The fracture properties of concrete of different sizes at different loading rates were studied by these authors (Bu et al, 2020;Ma et al, 2020;Zhang et al, 2008). These studies found that the peak load was proportional to the loading rate, and the loading rate had a great influence on large specimens.…”
Section: Introductionmentioning
confidence: 99%